Papel de los adyuvantes en la modulación de la respuesta inmune (2004)
ABSTRACT: The immunoprophylaxis is an important tool in the prevention of the infectious diseases; it depends of the capacity of the immune system to recognize and develop an effector response and immune memory against different stimulus. Currently, it is necessary to develop and improve the existent nonreplicating vaccines with the purpose to modulate and increase the immune response against a wide range of microorganisms or their antigens. The adjuvants constitutes an option to improve this type of vaccines because when they are incorporated in a vaccine formulation can enhance, accelerate or prolong the quality of the immune response to specific antigens. Adjuvants can be classified according to their action mechanisms into two types: immunoestimulatory and delivery systems. The immunoestimulatory adjuvants are derived from pathogens (lipopolysaccharides, CpG) and their function is to activate the innate immune cells. In contrast, the delivery systems are particles (emulsions, microparticles, ISCOMs) that transport and deliver an associated antigen to antigen-presenting cell. The discovery and development of new adjuvants opens the possibility to use new prophylactic and therapeutic vaccines against cancer, acute and chronic infectious diseases. These new vaccines will be more effective and safe to be used in human and animal species of economic importance.